Heterologous vaccine effects. Issue 34 (25th July 2016) - Saadatian-Elahi, Mitra; Aaby, Peter; Shann, Frank; Netea, Mihai G.; Levy, Ofer; Louis, Jacques; Picot, Valentina; Greenberg, Michael; Warren, William
Abstract: The heterologous or non-specific effects (NSEs) of vaccines, at times defined as "off-target effects" suggest that they can affect the immune response to organisms other than their pathogen-specific intended purpose. These NSEs have been the subject of clinical, immunological and epidemiological studies and are increasingly recognized as an important biological process by a growing group of immunologists and epidemiologists. Much remain to be learned about the extent and underlying mechanisms for these effects. The conference "Off-target effects of vaccination" held in Annecy-France (June 8–10 2015) intended to take a holistic approach drawing from the fields of immunology, systems biology, epidemiology, bioinformatics, public health and regulatory science to address fundamental questions of immunological mechanisms, as well as translational questions about vaccines NSEs. NSE observations were examined using case-studies on live attenuated vaccines and non-live vaccines followed by discussion of studies of possible biological mechanisms. Some possible pathways forward in the study of vaccines NSE were identified and discussed by the expert group.